Project Management Tools and Techniques and SME Performance: Empirical Evidence in the Context of Developing Countries - Sensini, Luca; Shan, Amit; Vazquez, Maria (International Journal of Economics and Financial Issues, 2021)
The goal of this article was twofold. The first objective was to investigate the diffusion and use of Project Management tools and techniques by manufacturing companies in an emerging economy, such as Argentina. The second objective was to assess the impact these instruments have on companies’ financial and non-financial performance. The companies selected for the analysis have their registered office in the province of Buenos Aires. Overall, 172 manufacturing companies participated in the survey. The research used a quantitative analysis methodology, using a questionnaire for data collection. The influence of Project Management tools on the performance of companies (users and non-users) was assessed using a non-parametric approach. Regarding the first objective of the research, the results showed that SMEs use a limited set of Project management tools and techniques. However, most managers have shown a strong focus on such tools. About the second objective, the results highlight positive and statistically significant relationships between most PM tools and business performance, suggesting that PM users perform better than non-users. The results show that the scoreboard has a positive impact on the financial and non-financial results of manufacturing firms. Configuration management and cost estimation techniques result in the higher financial performance of user companies than non-user companies. Besides, users of integrated logistics support have significantly better financial and non-financial performance than other companies. Keywords: Project management, Performance, SME, Emerging Economies JEL Classifications: G32, M16, M21 DOI: https://doi.org/10.32479/ijefi.11421